Improving the Students’ Vocabulary Mastery by Using Duolingo And Cake Applications - Ginting, Mayasari br; Sinambela, Erika; Manurung, Lastri Wahyuni (Institut Agama Islam Negeri Palopo, 2023)
The study concentrated on using the Cake and Duolingo apps to help students in the Rebecca Course and Center develop their vocabulary. The purpose of this study was to answer the following question: